2010
DOI: 10.5012/bkcs.2010.31.04.981
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of 2-Arylbenzothiazole Using Silica Sulfuric Acid under Microwave Irradiation

Abstract: The condensation of several aromatic/heteroaromatic aldehydes with 2-aminothiophenol catalyzed by silica sulfuric acid under microwave irradiation afforded 2-arylbenzothiazoles in high yields and short reaction times under solvent-free conditions. The major advantages of the present method are good yields, ecofriendly, reusable catalyst, mild and solvent-free reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…As previously suggested [37][38][39][40][41][42][43][44][45][46][47][48][49][50] , the reaction may proceed through the formation of imine I from aldehydes and 2-aminothiophenol. Subsequent cyclization to 2,3-dihydrobenzothiazole II followed by oxidation in air would afford 2-arylbenzothiazoles (Scheme 2).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As previously suggested [37][38][39][40][41][42][43][44][45][46][47][48][49][50] , the reaction may proceed through the formation of imine I from aldehydes and 2-aminothiophenol. Subsequent cyclization to 2,3-dihydrobenzothiazole II followed by oxidation in air would afford 2-arylbenzothiazoles (Scheme 2).…”
Section: Resultsmentioning
confidence: 93%
“…It has been shown that application of microwave irradiation reduce the reaction time and increases the product yield 49 . The use of domestic microwave ovens involves disadvantages such as: without control of temperature, power and pressure inside the reaction vessel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47][48][49][50][51][52][53][54][55] The salient catalytic activities attributed to silica sulfuric acid have encouraged us, in the second part of the present paper, to use various solvents like CH 3 CN, MeOH, H 2 O, EtOH, EtOAc, CH 2 Cl 2 and CCl 4 used for aromatization of 1,3,5-triphenyl-2-pyrazolines (1a) as model reaction, EtOH:H 2 O (10:1, v/v) was the solvent of choice as best results in terms of the yield was obtained using SSA (0.02 g), H 2 O 2 (1 mL) and KI (0.016 g) for 1 mmol of 1,3,5-triphenyl-2-pyrazolines when the reaction was run at 80 o C for 15 min in 90% yield (Table 3). Similarly, to illustrate the scope and usefulness of this methodology, a number of reactions were conducted (Scheme Literature data.…”
Section: Resultsmentioning
confidence: 99%
“…[7] One of the most common methods for the synthesis of benzothiazoles involves the direct condensation of the 2-aminothiophenol with aldehydes, carboxylic acids or its derivatives in the presence of various promoting agents, such as polyphosphoric acid (PPA), [8] polyphosphate ester, [9] a mixture of methanesulfonic acid and phosphorous pentoxide, [10] FeCl 3 , [11] Sc(OTf) 3 , [12] TCCA, [13] ionic liquid under microwave irradiation, [14] molecular iodine, [15] acetic acid under microwave irradiation [16] and silica sulfuric acid under microwave irradiation. [17] Some other general methods include palladium-catalyzed intramolecular cyclization of o-bromophenylthioureas, [18] Suzuki biaryl coupling of 2-bromobenzothiazole with arylboronic acids, [19] coupling of benzothiazoles with aryl bromides, [20] microwave-mediated reaction of 2-aminothiophenol with β-chlorocinnamaldehydes, [21] the reaction between thiophenols and aromatic nitriles, [22] and the intramolecular cyclization of thiobenzamides via aryl radical cations as reactive intermediates. [23] Very recently, we reported a method of preparing 2-substituted benzothiazoles from the reaction of 2,2 -disulfanediyldianiline with aldehydes promoted by sodium dithionite in water.…”
Section: Introductionmentioning
confidence: 99%